Enhancing cost efficiency and promoting sustainable development of rapeseed in China: the role of scale operations and management - Zhang, Qing; Ye, Feng; Tong, Ting; Feng, Zhongchao (Frontiers in Sustainable Food Systems, 2025)
IntroductionEnhancing cost efficiency and minimizing production expenses are pivotal for the long-term sustainability of China’s rapeseed industry. This study takes a comprehensive approach by integrating the Cobb–Douglas production function model with an advanced cost function model to empirically assess the influence of farm operation scale on the cost efficiency of rapeseed cultivation. Results reveal a non-linear relationship between the scale of operation and the average cost per mu: as the operational scale expanded, the average cost per mu initially decreased, then increased. Furthermore, economies of scale exhibit regional and topographical heterogeneity.MethodsDrawing on a robust dataset from 3,144 farmers across 14 key rapeseed-producing provinces in China, spanning from 2018 to 2021, our analysis uncovers a nuanced relationship between operational scale and production costs.Results and discussionThe findings indicate that as the scale of operation increases, the unit production cost initially declines, reaching a critical threshold before rising again, reflecting shifts in the production cost structure. This pattern is mirrored in the average cost efficiency loss per kilogram of rapeseed, which also shows an initial decrease followed by a subsequent increase. An analysis of regional heterogeneity reveals that in the eastern plains, the expansion of farm scale effectively curtails the excessive use of labor and seed inputs, leading to greater cost efficiency. Moreover, the findings also reveal that cost efficiency losses are consistently lower in the eastern regions compared to their central and western counterparts, and similarly, plains regions outperform non-plains regions in terms of cost efficiency. These insights offer valuable implications for policymakers and agricultural stakeholders aiming to optimize production practices and enhance the economic sustainability of rapeseed farming in China.